Labor Market Institutions and Flexibility in Italy : A Critical Evaluation and Some International Comparisons - Demekas, Dimitri (Washington, D.C. : International Monetary Fund, 1994)
The paper surveys three broad categories of labor market institutions in Italy: employment protection legislation, unemployment benefit systems, and wage bargaining arrangements. In each case, the recent evolution and current state of Italian institutions are evaluated and compared with those in other major European countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet